Malnutrition in patients with gastrointestinal cancer: effectiveness of different diagnostic methods - Prado, Corina Dias do [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP] (Aula Medica, 2015)
To estimate the effectiveness of methods for identifying the risk and/or presence of malnutrition in individuals with gastrointestinal neoplasia. participated 143 patients with gastrointestinal cancer, cared for in the Oncology Clinic Infirmary of Hospital Amaral Carvalho (Jaú-SP). Excluded from the study were patients hospitalized in the intensive care unit, in a terminal state or those who had members amputated; those who had received blood transfusions during the last month; significant clinical bleeding; received endovenous albumin and uncontrolled infection. The nutritional status was classified according to the ratio between Real Weight and Habitual Weight, Body Mass Index, Nutritional Risk Index and Percent Adequacy. As the gold standard method the Scored Patient-Generated Subjective Global Assessment was used. The effectiveness of the methods for detecting the risk for or presence of malnutrition was evaluated. A ROC curve was constructed and its area (AUROC) was estimated. The areas were compared using z statistics. For each method the best cut-off point was established. of the patients, 74.1% presented an advanced stage of the disease, and 83.2% were undergoing chemotherapy treatment. All the methods showed adequate discriminatory capacity for detecting the risk of malnutrition and presence of malnutrition. The BMI was significantly better for detecting malnutrition than for the risk of malnutrition. The RW/HW was significantly better for detecting the risk of malnutrition than the other methods. The cut-off points were slightly lower than those recommended for the normative population for the methods RW/HW, NRI and Score %. For the BMI the cut-off point was higher than the recommended for the normative population. the methods for evaluating nutritional status showed adequate discriminatory capacity for the risk of malnutrition and presence of malnutrition in patients with gastrointestinal cancer.

Objetivo: estimar la efectividad de los diferentes métodos para la identificación y/o presencia de desnutrición en las personas con riesgo de cáncer gastrointestinal. Métodos: los participantes fueron 143 pacientes con cáncer gastrointestinal, atendidos en la sala del Hospital Clínico de Oncología Amaral Carvalho (Jau-SP). No se excluyeron los pacientes ingresados en la unidad de cuidados intensivos, con enfermedad terminal o con miembros amputados que recibieron transfusiones de sangre en el último mes, con hemorragias clínicamente relevantes, que recibieron albúmina intravenosa y aquellos con infección no controlada. El estado nutricional de los participantes se clasificó de acuerdo a la relación Peso Real y Peso Habitual (PR/PH), Índice de Masa Corporal (IMC), Índice de Riesgo Nutricional (IRN) y porcentaje de ajuste (% score). Como método estándar de oro se utilizó la Evaluación Global Subjetiva. Fue evaluada la eficacia de los métodos para detectar el riesgo de desnutrición o la presencia de desnutrición. La curva ROC fue construido y su área (AUROC) se estimó. Las áreas se compararon mendiante z estadística. Para cada método resuelto el mejor punto de corte. Resultados: de los pacientes, el 74,1% había avanzado en el estado de la enfermedad y el 83,2% fueron sometidos a métodos quimioterápicos. Todos los métodos de tratamiento mostraron una adecuada capacidad discriminatoria para detectar el riesgo de desnutrición y la presencia de la misma. El IMC fue significativamente mejor para la detección de la desnutrición que para el riesgo de desnutrición. El riesgo PR/PH fue significativamente mejor para detectar el riesgo de desnutrición que otros métodos. Los puntos de corte fueron inferiores a los puntos de corte recomendados para población normativa con los métodos PR/PH, NRI y porcentaje de ajuste (% score). Para el punto de corte del IMC fue mayor que el recomendado para la población normativa. Conclusión: los métodos de evaluación del estado nutricional mostraron una capacidad discriminatoria adecuada del riesgo de desnutrición y de la presencia de desnutrición en pacientes con cáncer gastrointestinal.
La desnutrición en pacientes con cáncer gastrointestinal: efectividad de diferentes métodos de diagnóstico